2017
DOI: 10.2147/ijn.s132778
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporosity improved water absorption, in vitro degradability, mineralization, osteoblast responses and drug release of poly(butylene succinate)-based composite scaffolds containing nanoporous magnesium silicate compared with magnesium silicate

Abstract: Bioactive composite macroporous scaffold containing nanoporosity was prepared by incorporation of nanoporous magnesium silicate (NMS) into poly(butylene succinate) (PBSu) using solvent casting–particulate leaching method. The results showed that the water absorption and in vitro degradability of NMS/PBSu composite (NMPC) scaffold significantly improved compared with magnesium silicate (MS)/PBSu composite (MPC) scaffold. In addition, the NMPC scaffold showed improved apatite mineralization ability, indicating b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The ALP activity was measured with the ALP assay at 7 and 10 days after treatment with osteogenic differentiation medium. The assays were performed as previously described 54 . The ALP activity was expressed as the OD value per the total protein amount, which was determined using BCA protein assay kits and a series of BSA standards.…”
Section: Methodsmentioning
confidence: 99%
“…The ALP activity was measured with the ALP assay at 7 and 10 days after treatment with osteogenic differentiation medium. The assays were performed as previously described 54 . The ALP activity was expressed as the OD value per the total protein amount, which was determined using BCA protein assay kits and a series of BSA standards.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the scaffolds were immersed in PBS (pH 7.2) and incubated at 37 • C for 1 h. The excessive liquid from the sponge scaffolds surface were gently removed using filter paper, followed by weighing to obtain the weight after swelling (S s ). The water uptake ability was evaluated after incubation for 48 h at 37 • C to permit water adsorption therefore as mentioned in previous publication [25] the sponges were initially weighed to obtain their dry weight (W d ) followed by weighing to obtain their weight after water uptake (W s ). The swelling ratio and water uptake were calculated using the equations below:…”
Section: Swelling Ratio and Water Uptake Abilitymentioning
confidence: 99%
“…Nanoporous magnesium silicate (nMS) is a bioactive glass that possesses a nanoporous structure with large surface area and high pore volume 18. Our previous research has confirmed that the nMS exhibits superior in vitro bioactivity, cytocompatibility, and in vivo osteogenesis 19…”
Section: Introductionmentioning
confidence: 93%